STRATEGI PENGUATAN SISTEM PENGENDALIAN INTERNAL UNTUK MENGHINDARI TERJADINYA FRAUD PADA KAS PERUSAHAAN - Puput Yulan; Iwan Setya Putra (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2021)
Abstract. The research objective is to analyze the problem of how to analyze internal cash controls by PT. Era Jaya Wijaya Blitar analyzes to support the effectiveness of cash management. The purpose of writing this thesis is to analyze the internal control of cash by PT. Era Jaya Wijaya Blitar in supporting the effectiveness of cash management. The type of research that will be used is descriptive quantitative. Descriptive analysis was carried out by collecting data obtained from the source then followed by interviews and observations of the actual situation. There are 2 variables used in this study, namely, internal cash control and the effectiveness of cash management. Some of the research methods used include interviews, observation and documentation. Based on the research results, cash management conducted by PT. Era Jaya Wijaya Blitar is not yet effective. This is reflected in the absence of segregation of the functions of supervision, recording, and storage in cash as well as in dual work, the filling of transaction proof numbers for most cash receipts and disbursements documents is still filled in manually, not using printed serial numbers. As for the internal cash control activities set by PT. Era Jaya Wijaya Blitar has not been effective, proven by the fact that there are still elements of internal control that have not been implemented in the company, such as the absence of a separation of supervision functions from cash recording and storage.